Corruption v democracy - part two: Democratic institutions fight back - Lewis, David (New Agenda: South African Journal of Social and Economic Policy, 2024)
In part two, DAVID LEWIS returns to the question of the relationship between democracy and corruption and argues that for political corruption on the scale he describes in part one to thrive with impunity, democracy would have to be hollowed out.